-6(2-3x)-3=-15+2x

Simple and best practice solution for -6(2-3x)-3=-15+2x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6(2-3x)-3=-15+2x equation:


Simplifying
-6(2 + -3x) + -3 = -15 + 2x
(2 * -6 + -3x * -6) + -3 = -15 + 2x
(-12 + 18x) + -3 = -15 + 2x

Reorder the terms:
-12 + -3 + 18x = -15 + 2x

Combine like terms: -12 + -3 = -15
-15 + 18x = -15 + 2x

Add '15' to each side of the equation.
-15 + 15 + 18x = -15 + 15 + 2x

Combine like terms: -15 + 15 = 0
0 + 18x = -15 + 15 + 2x
18x = -15 + 15 + 2x

Combine like terms: -15 + 15 = 0
18x = 0 + 2x
18x = 2x

Solving
18x = 2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
18x + -2x = 2x + -2x

Combine like terms: 18x + -2x = 16x
16x = 2x + -2x

Combine like terms: 2x + -2x = 0
16x = 0

Divide each side by '16'.
x = 0

Simplifying
x = 0

See similar equations:

| (-3)*(-3)*(-3)+x=10x | | p/4-1=3 | | 4.7x+3.8=13.2l | | -2v+5v=-12 | | 445.53=.71x | | d/3-6=-2 | | X/8=21/14 | | x/4-9=-11 | | 5n-5=5n+10 | | 2/5*25=10 | | 4x+6y=4200 | | -11x=17 | | 2x-66=12 | | 7d+3=94 | | -9=-2v+5 | | 1/3xyz=p | | h/4-6=-1 | | 22-5p=57 | | q/8-1=2 | | 8x+4=92 | | 4x-6-2x=4 | | Q-1/21/2 | | -5+2m=25 | | 5=n/2-5 | | 6+6d=54 | | 8x-9=143 | | z/3-1=1 | | 5x-4+6x-9-4=2+2x+7 | | -2+10n=78 | | 2x+3-7(x-1)=2(x-55)+5x | | 1/7f-5(1/5)=9/14 | | a/6-1=2 |

Equations solver categories